KEGIATAN PELATIHAN MEMBACA DAN MENULIS AL-QUR’AN UNTUK MENINGKATKAN KETERAMPILAN SANTRI TPQ AT TAQWA DESA PENJARINGAN, KECAMATAN RUNGKUT SURABAYA - Muhammad Yusron Maulana El-Yunusi; Mirza Elmy Safira; Zidni Akholik Almaghfiroh; Nadia Wulidar Rohmah (STKIP PGRI SITUBONDO, 2025)
The ability to read and write the Qur'an is a basic competency that students must have from an early age as a foundation for developing religious character. However, many students at the Al-Qur'an Education Park (TPQ) still experience difficulties in reading the Qur'an according to the rules of tajwid and writing the hijaiyah letters correctly. This community service activity aims to improve the reading and writing skills of the Qur'an of students at the At-Taqwa TPQ in Penjaringan Village, Rungkut District, through a structured and interactive training program. The method used is the Asset Based Community Development (ABCD) approach by utilizing local potential, involving students, TPQ teachers, students, and community support. The training was carried out for two days, including observation, material delivery, direct practice, and intensive mentoring. The results of the activity showed an increase in the students' ability to read the Qur'an with more precise makharijul huruf and tajwid as well as better ability to write the hijaiyah letters. The percentage of students who experienced difficulties in reading and writing the Qur'an decreased from around 60% to 30% after the training. In addition to improving skills, this activity also increases students' motivation to learn and parental involvement in Quranic education. This program is expected to serve as a model for the sustainable development of Quranic learning at TPQ (Islamic boarding schools) to strengthen Quranic literacy and Islamic values ​​in the community